2017
DOI: 10.1016/j.celrep.2017.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Primer-Independent DNA Synthesis by a Family B DNA Polymerase from Self-Replicating Mobile Genetic Elements

Abstract: SummaryFamily B DNA polymerases (PolBs) play a central role during replication of viral and cellular chromosomes. Here, we report the discovery of a third major group of PolBs, which we denote primer-independent PolB (piPolB), that might be a link between the previously known protein-primed and RNA/DNA-primed PolBs. PiPolBs are encoded by highly diverse mobile genetic elements, pipolins, integrated in the genomes of diverse bacteria and also present as circular plasmids in mitochondria. Biochemical characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 74 publications
(90 reference statements)
4
61
0
Order By: Relevance
“…In some genomes, three att-repeats were detected, as those pipolins seem to share the integration site and mechanism with some prophage, as previously detected for the enterotoxigenic Escherichia coli H10407 strain [3]. Indeed, comparison of the genetic structure of all pipolins ( Figure S5), confirmed that a similar myovirus enterophage is present next to pipolins from eight strains, spanning phylogroups A (H10407, 2014EL-1346-6 and 99-3165), C (LREC239 and LREC246) and D (112648, 122715, 2015C-3125 and FWSEC0002).…”
Section: Mapping and Extraction Of New Pipolins From Lrec And Genbanksupporting
confidence: 63%
See 2 more Smart Citations
“…In some genomes, three att-repeats were detected, as those pipolins seem to share the integration site and mechanism with some prophage, as previously detected for the enterotoxigenic Escherichia coli H10407 strain [3]. Indeed, comparison of the genetic structure of all pipolins ( Figure S5), confirmed that a similar myovirus enterophage is present next to pipolins from eight strains, spanning phylogroups A (H10407, 2014EL-1346-6 and 99-3165), C (LREC239 and LREC246) and D (112648, 122715, 2015C-3125 and FWSEC0002).…”
Section: Mapping and Extraction Of New Pipolins From Lrec And Genbanksupporting
confidence: 63%
“…This analysis showed that an important proportion of pipolins from phylogroups C and D, but Overall, we can conclude that the pipolins diversity is poorly congruent with the strains phylogeny and their distribution is rather indicative of a patchy distribution amongst a wide variety of pathogenic E. coli strains, as expected from horizontally transferred MGEs. This pattern may reflect the wide distribution of pipolins beyond E. coli, dispersed among major bacterial phyla, namely Actinobacteria, Firmicutes, and Proteobacteria, as well as in mitochondria [3]. Tanglegram representation of maximum-likelihood comparative phylogenies of piPolB and host strains core genome as hallmark of pipolins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to insufficient sampling or to genuine lack of these elements in this archaeal phylum. By contrast, bacteria are known to (Nicolas et al, 2015); various pathogenicity islands and phage-inducible chromosomal islands that are induced upon phage infection and hijack the virus particle for intercellular transmission (Novick and Ram, 2016;; mobile integrons, complex genetic platforms that allow bacteria to evolve rapidly through the acquisition, excision and shuffling of genes found in mobile elements known as cassettes (Escudero et al, 2015); or pipolins, a recently characterized group of bacterial iMGE encoding primer-independent DNA polymerases (Redrejo-Rodríguez et al, 2017). However, given our limited understanding on the archaeal mobilome and especially the diversity of iMGE, it cannot be ruled out that counterparts to some of these bacterial iMGE classes in thaumarchaea are awaiting discovery.…”
Section: Discussionmentioning
confidence: 99%
“…This complexity may be reduced by exploiting more minimal replisomes, for example those of infective viruses or phages. [141] Bacteriophage Phi29 from B. subtilis initiates replication by a protein-priming mechanism enabling a minimal set of four Phi29 replication proteins to suffice for in vitro amplification of heterologous DNA. [139] The T7 phage, infecting E. coli, uses a host component for processivity and can carry out the replication of duplex DNA with a minimum of four core components.…”
Section: Self-encoded Dna Replicationmentioning
confidence: 99%